Die Landshuter Buchdrucker des 16. Jahrhunderts : Mit einem Anhang: Die Apianusdruckerei in Ingolstadt - Schottenloher, Karl, (European History and Culture - Book Archive pre-2000., 1967)
More than 235 entries, the great majority of which are imprints by Johann Weyssenburger.